Juventude e escola: reflexões dos jovens em torno da relação professor/aluno - Fernanda Cristina Soares Silvino (2009)
This research is proposed to undertake a study on the relationship youth / school. In a more specific way, exam the relationship between students and teachers in a night period high school trying to understand the construction of ratings assigned by students to teachers. In the context of the expansion of education and its consequences in everyday school, several issues are raised, such as: The reality of students who come to school has affected the relationship with the school establish its teachers? How to make the relationship of these students and their teachers in the context of the classroom? As the students construct the meanings they attach to their teachers? What factors interfere with the construction of this classification? What is the meaning that the school has on the lives of these students? To examine these issues, we developed an empirical research in a class of second year of public night period high school, where data were collected through observation of everyday school life, questionnaires and interviews. The data were analyzed in the focus of sociology of education, by authors such as Dubet (2005), Perrenoud (1995), Sposito (2005), Abrantes (2003) Dayrell(2001 and 2007), Souza (2003), among others. The data analysis revealed, among other things, that to the students surveyed the school presents an instrumental dimension, where the purpose of study is made in acquiring the certification, considered important goal for apossible improvement in the future. At the same time value the daily school attendance especially by the size of the meeting with friends. For these students, the relationship with teachers is very valuable, interfering directly in the learning process. But there is a classification of diverse faculty, with the presence of multiple variables. The considered goodteacher, for example, were those that come closest to their students and seeking to understand the difficulties and needs of them.